Dietary Habit and Physical Activity as Risk Factors of Metabolic Syndrome among Civil Servants in Jambi City - Guspianto Guspianto; Ismi Nurwaqiah Ibnu; Puspita Sari; Zavira Nadwa (Media Kesehatan Masyarakat Indonesia, 2024)
The prevalence of Metabolic Syndrome (MetS) is an important health problem due to the association with increased cardiovascular disease as the main cause of death. Approximately 20-25% of the global adult population including Indonesia suffers from MetS. The high prevalence is attributed to several factors namely lifestyle changes such as dietary habit and physical activity. Therefore, this study aimed to investigate the relationship between dietary habit and physical activity with MetS incidence among civil servant employees in Jambi City, Indonesia. A cross-sectional design was used to assess the proportion of MetS, dietary habit, and physical activity. A total of 108 civil servant employees were selected as respondents from six agencies using a multistage random sampling technique. Data collection was carried out through physical examination and interviews using a questionnaire. The results showed that the prevalence of MetS was 60.2%, with three risk indicators, namely central obesity (74.1%), blood pressure (66.7%), and HDL (63%). Based on the chi-square test, dietary habit (OR=2.571, 95%CI=1.151-5.744) and physical activity (OR=3.692, 95%CI=1.625-8.388) were significantly related to MetS. The persistently high prevalence of MetS was significantly related to dietary habit and physical activity among civil servant employees in Jambi City-Indonesia. These results underscored the need to improve understanding of healthy diets by adopting a balanced nutritional intake, increasing the intensity of physical activity according to age, and engaging in regular exercise.